An analysis of public-private partnerships in housing in the Zimbabwe National Housing Delivery Programme: a case of Masvingo City - Chikomwe, Savory (University of the Witwatersrand, Johannesburg, 2014)
Based on evidence of the performance of a public-private partnership (PPP) housing arrangement in Masvingo City, Zimbabwe, I argue that PPPs may not thrive in youthful democracies entrenched in informal approaches to project management. The PPP strategy which was meant to deliver about 10 000 housing units in Masvingo City has dismally failed to live to its expectation, save for an ignited spirit of cooperativism. This is in spite of what was dubbed as a potentially promising partnership strategy involving indigenous private developers and contractors. Yet the compulsory acquisition of urban and peri-urban farmland country-wide presented powerful launch pad for a promisingly successful housing delivery that is widely expected to wipe out serious housing deficits. Housing problems were recently further compounded by Operation Murambatsvina in 2005 which ruthlessly demolished all informal housing and left several hundreds of thousands homeless. Following an insightful in-depth interview methodology and several ground-truthing trips to the Victoria Ranch Housing Project site, I argue that Government of Zimbabwe (GOZ) arrangements in terms of legal, administrative and financial aspects were weak to enable successful implementation of a formal PPP strategy. The arrangements advertently or inadvertently promoted privatism instead of the mutually beneficial PPP arrangement. As such, there were no clear regulatory mechanisms and modalities to enable beneficiation of the targeted low-income people and other economically weaker sections of the Masvingo City Community. There are fears that undeserving better-offs could have hijacked the scheme. However, a commendable resilience has emerged through a resurgent self-help housing delivery approach resulting in many self-built houses in what is widely viewed as a “peculiar” parallel development. While it could be too early to meaningfully comment on the long-term performance of the PPP approach, it is clear that justice has not been done to low-income people in Masvingo who remain largely homeless.
A research report presented in fulfilment of the requirement of the Master of Science (Housing) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, 2014.
Keywords: Public-private partnership (PPP) housing; Zimbabwe; UCTD; Masvingo City; City planning; Community development; Housing